Implementasi Pengaturan Traditional Fishing Rights Dalam Hukum Indonesia - Magdariza, Magdariza (Faculty of Law, Andalas University, 2024)
The concept of an archipelagic state as regulated in chapter IV of the 1982 Convention on the Law of the Sea, called the United Nations Convention On The Law Of The Sea/UNCLOS, was the struggle of several archipelagic countries when an international conference on the law of the sea was held. The Convention stipulates that island states, in exercising sovereignty in certain parts of their territorial waters, must recognize the traditional rights of the people of neighboring island states. These traditional rights are called traditional fishing rights, which are implemented in a certain part of the archipelagic waters of an archipelago. This right is a right that has been carried out for a long time from generation to generation and is carried out using traditional criteria, including that the users of this right are traditional communities, carried out using traditional tools and methods, and the place of implementation is in certain areas of the archipelagic waters of archipelagic countries. This right can only be enjoyed if an agreement has been made between the archipelagic country and its neighboring countries. The provisions regarding traditional fishing rights can be seen in article 47 paragraph 6 and article 51 paragraph 1 of the Convention. Indonesia, as an archipelagic country, has an obligation to recognize and respect traditional fishing rights, and has entered into agreements with several of Indonesia's neighbors, including Malaysia, Papua New Guinea and Australia. These various agreements have also been implemented in Indonesian national law by ratifying these various agreements.